PERAN IDEAL TIM PENGAWASAN ORANG ASING DALAM PENGAWASAN TENAGA KERJA ASING DI INDONESIA (Studi Kasus di Kantor Imigrasi Kelas 1 Surakarta) - Romadhon, Romadhon; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This legal research examines the role of supervision of the Foreigners Oversight Team in the supervision of Foreign Workers in the working area of the Class 1 Surakarta Immigration Office based on Law Number 6 Year 2011 concerning Immigration. This research is normative legal research supported by data in the field. This research is a descriptive legal research, with a legal approach and analytical approach. The types of data collected are primary legal material and secondary legal material. Data collection techniques used were interviews and literature studies. Based on the results of the study, the supervision of the Foreigners’ Oversight Team in the supervision of Foreign Workers in the working area of the Surakarta Class 1 Immigration Office is in accordance with the Immigration Act. The problem that arises in supervision is related to the existing legislative system in Indonesia which still provides a gap to be broken, this is indicated by the misuse of visit residency that is used to work as many as 20 people during the 2017-2018 period, members of the Foreign Persons Control Team say this cannot be released from Presidential Regulation No. 21 of 2016 concerning Visit Visa Free, besides also the factor of Guarantor or Sponsor who does not comply with existing regulations plus law enforcement officials who are still unprofessional is an obstacle in the enforcement of illegal Foreign Workers.